Evidence for marine-driven, cyclical fluctuations in burrow-nesting seabird habitat on the Oregon Coast - Kusaka, Carina M.; Stephensen, Shawn; Peterson, James T.; Davis, Melanie J. (Frontiers in Ecology and Evolution, 2025)
Seabirds are among the most threatened birds globally, with the loss or deterioration of coastal breeding habitats posing a severe threat. Natural and anthropogenic disturbances substantially influence coastal ecosystems through erosion and vegetation loss, altering habitat for the wildlife species that depend on them. In addition to these disturbances, oceanographic processes may play an important role in shaping the vegetation at breeding habitats; however, there is limited information on how vegetative conditions for burrow nesting seabirds have changed over time, and whether these changes are related to specific oceanographic or climatic factors. The Oregon Coast National Wildlife Refuge Complex, USA (NWRC) is home to a diverse suite of 1.3 million nesting seabirds from 14 species, which provide valuable ecological, economic, and cultural services, including nutrient transfer to terrestrial habitats and ecotourism for local communities. Over the last 30 years, populations of several burrow nesting seabird species including tufted puffin (Fratercula cirrhata) and rhinoceros auklet (Cerorhinca monocerata), which breed on offshore islands, have sharply declined along the Oregon Coast. To better understand the potential factors driving these declines, we conducted a spatiotemporal analysis of an aspect of burrow nesting seabird habitat, vegetation cover, within the Oregon Coast NWRC. Specifically, we quantified vegetative cover on 16 islands from 1992 to 2022 using a combination of empirical data, historical aerial photography (1992–2005), and aerial photography from the National Agriculture Imagery Program (2005–2022). Results showed cyclical fluctuations in vegetation cover coast-wide, which were closely related to large scale oceanographic oscillations. Specifically, vegetation cover was negatively correlated with the winter Pacific Decadal Oscillation and positively correlated with the spring El Nino Southern Oscillation. We did not directly compare seabird population trends to vegetation trends; however, quantifying these long-term changes in vegetation at breeding habitats can contribute to our comprehensive understanding of the myriad factors influencing seabird population dynamics and conservation.